Establishing and validation of new critical limits of zinc for Tomato (Solanum lycopersicum L.) in Alfisols of Karnataka, India. (3rd July 2022) - Prasad, Pothagani N. Siva; Thimmappa Subbarayappa, Chickadibburahalli; Sathish, Ayyappa; Ramamurthy, Venkataramanappa
Abstract: Critical limit (CL) determination of zinc (Zn) is much more important to assess the response of crop to its application in soils and for crops actual fertilizer requirement. This experiment was conducted at University of Agricultural Sciences, Bangalore in sandy clay loam texture soils. Based on the results of the pot culture experiment, the critical limits of DTPA, AB-DTPA, Mehlich-3, tomato plant and tomato fruit are 1.12, 1.20, 2.15, 34 and 58 mg kg −1, respectively. Tomato was highly responded to Zn application in soils below the critical limit whereas soils with Zn greater than 1.12 mg kg −1 did not respond much. For the confirmation of pot culture results, two field experiments were carried out during 2017–18 with different Zn treatments one in high and other in low zinc soils. The study concluded that for both low zinc and high zinc soils external application of zinc through Recommended dose of fertilizers (RDF) + ZnSO4 @ 30 kg ha −1 as soil application (SA) + foliar application (FA) @ 0.50% ZnSO4 and RDF + ZnSO4 @ 20 kg ha −1 as SA + FA @ 0.25% ZnSO4 significantly improved yield, nutrient concentration and uptake of nutrients, which helped in getting higher benefit cost (B:C) ratio of 4.74 and 4.96, respectively. This information is helpful in site-specific zinc nutrition in tomato and to enhance the productivity and profitability.